2012
DOI: 10.2147/coaya.s27725
|View full text |Cite
|
Sign up to set email alerts
|

New treatment options for nonmetastatic osteosarcoma: focus on mifamurtide in adolescents

Abstract: New treatments are needed to improve the clinical outcome for patients with osteosarcoma. Liposomal muramyl tripeptide phosphatidylethanolamine (mifamurtide) is a synthetic peptidoglycan component packaged in multilamellar liposomes. Mifamurtide has been demonstrated to induce recruitment and activation of macrophages and monocytes of the host innate immune system, which leads to antitumoricidal activity. Early clinical trials have demonstrated the safety and tolerability of mifamurtide combined with chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Most patients could also be successfully weaned off these pre‐/post‐medications to try to maximize biologic effectiveness of mifamurtide while having a good quality of life on the drug. Flow diagrams concerning recommended use of pre‐ and post‐medications have been recently published as well as a review of current status of mifamurtide .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients could also be successfully weaned off these pre‐/post‐medications to try to maximize biologic effectiveness of mifamurtide while having a good quality of life on the drug. Flow diagrams concerning recommended use of pre‐ and post‐medications have been recently published as well as a review of current status of mifamurtide .…”
Section: Discussionmentioning
confidence: 99%
“…A separate analysis of a smaller cohort in this study who presented with metastatic disease showed the possibility of a larger treatment effect: 13% improved overall survival rate at 5 years; however, because of small numbers (N ¼ 91) this did not reach statistical significance [32]. Thus, multiple levels of evidence suggest that mifamurtide, when combined with chemotherapy, can improve osteosarcoma survival [40][41][42]. The drug is currently available for clinical use in Europe, Mexico, South Korea, Switzerland, and Israel for non-metastatic osteosarcoma.…”
Section: Introductionmentioning
confidence: 97%
“…In 2009 mifamurtide was approved by the European Medical Agency for the treatment of high-grade non-metastatic resectable osteosarcoma following surgical removal in children, adolescents and young adults. 239 , 242 244 This approval was prompted by the promising data generated from a large phase III randomized prospective intergroup trial. 245 Results showed that intravenous treatment with mifamurtide after complete surgical resection and postoperative multi-agent chemotherapy significantly improved the six-year overall survival from 70% to 78% in patients with newly diagnosed osteosarcoma; patients with metastatic disease showed improvement in five-year overall survival from 40% to 53%.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“… 246 , 247 Mifamurtide is generally well tolerated, with reported adverse effects including fever, chills, nausea, headache, fatigue and myalgias. 242 , 243 , 248 Although mifamurtide is not yet approved in the US, several trials [ClinicalTrials.gov identifier: NCT014559484] are currently underway to further investigate its efficacy in osteosarcoma. 239 …”
Section: Targeted Therapiesmentioning
confidence: 99%
“…A Phase III, randomized, prospective intergroup trial (INT-0133) study of mifamurtide on patients with newly diagnosed osteosarcoma, showed significant improvement in six-year overall survival from 70% to 78% and in patients with metastatic disease showed improvement in five-year overall survival from 40% to 53% [ 32 , 33 ]. Numerous studies have reported of promising clinical benefits when mifamurtide is combined with chemotherapy in treatment of metastatic OS [ 34 ]. The drug has been currently approved as an adjuvant treatment of osteosarcoma by European Medical Agency, but has not been approved by the US FDA.…”
Section: Immunomodulatorsmentioning
confidence: 99%